Relevansi Teori Hierarki Kebutuhan Abraham Maslow Terhadap Motivasi Kerja Anggota Organisasi Penyuluhan Agama Islam - Muhammad Ali Bagas (Prodi Bimbingan dan Konseling Islam, 2020)
This study aims to describe the relevance of Abraham Maslow's hierarchy of needs theory with the work motivation fellow of Islamic counseling organizations. The research used is; library research that using content analysis as a technique in analyzing related data. The results of this study, namely; Fulfilling the needs of each fellow Islamic counseling organization are one of the causes that can describe the ups and downs of work motivation fellow. The fulfillment needs to be referred to here, namely; needs formulated by Abraham Maslow, the physiological needs, the safety needs, the belongingness and love needs, the esteem needs, and the need for self-actualization.